Синтез некоторых новых 2,2-дизамещенных производных 1,4-бензодиоксана - Авакян, А. С.; Вартанян, С. О.; Саргсян, А. Б.; Агекян, А. А. («Գիտություն» հրատ.)
Ուսումնասիրվել են 2,2-երկտեղակալված 1,4-բենզոդիօքսանի որոշ ածանցյալների սինթեզի ուղիները: Բրոմացման ռեակցիայի և հետագա մեթօքսիլացման միջոցով ստացվել է 2-մեթօքսի-1,4-բենզոդիօքսան-2-կարբոնաթթվի մեթիլէսթերը, որը, փոխազդելով հիդրազինհիդրատի հետ, առաջացրել է համապատասխան թթվի հիդրազիդը, վերջինի ցիկլացման արդյունքում սինթեզվել է 5-(2-մեթօքսի-1,4-μենզոդիօքսան-2-իլ)-1,3,4-օքսադիազոլ-2-թիոլ: Միջանկյալ 2-բրոմտեղակալված միացություն պարունակող խառնուրդից թիոմիզանյութի հետ եռացման պայմաններում ստացվել է նոր սպիրոցիկլային միացություն՝ 2՚-ամինո-3Н,4՚Н-սպիրո(μենզո[b][1,4]դիօքսին-2,5-՚թիազոլ)-4՚-ոն: The methods for the synthesis of 2,2-disubstituted derivatives of 1,4-benzodioxane – the analogous of α2-adrenoblocator idazoxan, involving 1,4-benzodioxane and 5-membered heterocycle, have been investigated. By bromination and methoxylation reactions the methyl ether of 2-methoxy-1,4-benzodioxan-2-carboxylic acid was synthesized. By interaction with hydrazine hydrate followed by cyclization, the 5-(2-methoxy-1,4-benzodioxan-2-yl)-1,3,4-oxadiazol-2-thiol was obtained. The intermediate product containing Br-substituted compound by heating with thiourea in acetone was converted to the spirocyclic compound - 2'-amino-3H,4'H-spiro[benzo[b][1,4]dioxine-2,5'-thiazol]-4'-one. The structures of synthesized compounds were confirmed by physicochemical methods and thin-layer chromatography.
Keywords: Քիմիա